Antibiotic Resistance in Nosocomial Bacteria Isolated from Infected Wounds of Hospitalized Patients in Czech Republic - Kolar, Milan; Cermak, Pavel; Hobzova, Lenka; Bogdanova, Katerina; Neradova, Katerina; Mlynarcik, Patrik; Bostik, Pavel (Antibiotics (Basel, Switzerland), 2020)
Hospitalized patients with wounds face an increased risk of infection with multi-drug-resistant nosocomial bacteria. In this study, samples from almost 10,000 patients from big hospitals in Czech Republic with infected wounds were analyzed for the presence of bacterial pathogens. In 7693 patients (78.8%), bacterial etiological agents were identified. Members of the Enterobacterales (37.1%) and Staphyloccus aureus (21.1%) were the most prevalent pathogens. Staphyloccus aureus showed methicillin resistance in 8.6%. Almost half of the Klebsiella pneumoniae isolates were ESBL-positive and 25.6% of the Enterobacter spp. isolates were AmpC-positive. The third most prevalent Pseudomonas aeruginosa showed resistance to 19-32% of the antipseudomonal antibiotics tested. Based on the results, amoxicillin/clavulanic acid, ampicillin/sulbactam or piperacillin/tazobactam combined with gentamicin can be recommended for antibiotic treatment of infected wounds. Once the etiological agent is identified, the therapy should be adjusted according to the species and its resistance.
Keywords: resistance; nosocomial; wound infection